Creating Shared Value-Based Marketing: Integrating Economic, Social, and Business Value in MSME Partnerships - Wahyudin Rahman; Sutrisno K Djawa; Pardin Lasaki (Jurnal Manajemen Bisnis, 2026)
This study examines how Creating Shared Value (CSV) principles, CSV-based marketing strategy, the integration of economic, social, and business value, and stakeholder engagement with sustainable marketing are associated with the perceived effectiveness of CSV implementation among micro, small, and medium enterprise (MSME) partners of JOB Tomori Sulawesi. An explanatory cross-sectional survey was conducted with 250 MSME owners or managers selected purposively from an estimated population of 540 active partners. Data were collected through a 50-item questionnaire using a five-point Likert scale. Item-total correlations, Cronbach's alpha, Harman's single-factor test, descriptive statistics, and multiple linear regression were used to assess the measurement quality and test the hypotheses. All constructs demonstrated acceptable validity and reliability, with item-total correlations ranging from 0.715 to 0.824 and Cronbach's alpha values ranging from 0.861 to 0.917. The model explained 71.2% of the variance in perceived CSV implementation effectiveness. CSV-based marketing strategy had the largest standardized association (beta = 0.267, p = 0.001), followed by CSV principle implementation (beta = 0.241, p = 0.002), stakeholder engagement and sustainable marketing (beta = 0.213, p = 0.004), and economic, social, and business value integration (beta = 0.198, p = 0.005). The findings indicate that CSV is most effective when social objectives are embedded in market access, local supply chains, product development, and stakeholder relationships rather than treated as separate philanthropic activities. Because the study is cross-sectional, self-reported, and limited to one project setting, the results should be interpreted as predictive associations rather than causal effects.